PENERAPAN PROBLEM BASED LEARNING PADA MATERI PERTIDAKSAMAAN RASIONAL PADA SISWA KELAS X MA - Putri, Faradhilah Saskiyah; Satiti, Wisnu Siwi; Rohmah, Hidayatur (Exact Papers in Compilation (EPiC), 2019)
This study aims to describe the application of problem based learning in the material rational inequality in class X MA. This research uses quantitative methods with one-shot case study design. Data collection methods used in this study are tests in the form of pre-test and post-test. The data analysis technique used is the paired sample t-test method. Based on the analysis using SPSS obtained sig. (2-tailed) of 0,000 < α = 0.05. Thus Ho is rejected and Ha is accepted, ie there is a difference between the average pretest results and the average posttest results. so that effective problem based learning is applied in class X MA. Keywords: Problem based learning, rational inequality, one shot case study